A STUDY ON CHRONIC EFFECT OF PROFENOFOS ON ACETYLCHOLINESTERASE AND BUTYRYLCHOLINESTERASE ACTIVITIES AND PROTEIN CONTENTS IN VARIOUS TISSUES IN MAJOR CARPS - Ghazala, Ghazala; Mahboob, Shahid; Al-Ghanim, K. A.; Sultana, Salma; Sultana, Tayyaba; Almisned, F.; Ahmed, L.; Shahid, Tehniat; Ahmad, Zubair (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Pesticides widely used for agricultural purposes are carbamates, organophosphates as well as organochlorines. Amongthese pesticides, organochlorine compounds have been extensively used to control disease vectors as well as agricultural pests. Theobjective of this experiment was to study the chronic effect of a commercial formulation of profenofos on acetylcholinesterase (AChE)and butylcholinesterase (BuChE) activity in various tissues in Catla catla, Labeo rohita and Cirrhinus mrigala fingerlings wasinvestigated.Materials and Methods: Healthy fingerlings of Catla catla, Labeo rohita and Cirrhinus mrigala with an average body length 90±6 mmand 30.00±2.00 g body weight were collected from the fish seed hatchery and brought to the laboratory. Fishes were maintained in 70litter glass aquaria (27 ± 1oC, 2.70–2.80 ms and 8.85–9.40 pH). The fingerlings of Catla catla, Labeo rohita and Cirrhinus mrigala wereexposed to the 3 sub lethal concentrations of profenofos (0.038, 0.019, 0.012; 0.06, 0.03, 0.02 and 0.041, 0.020 and 0.013 mg/L) for 8weeks. The control experiments were also performed with the addition of carrier solvent alone. Acetylcholinesterase andbutyrylcholinesterase level were estimated according to the methodology of Ellman et al. (1961) and Kuster (2005). Total solubleproteins were determined by the Bradford (1976) standard method to assess enzymatic activity of the protein.Results: The least activity of AChE was recorded in muscle samples of Catla catla (1.07±0.040 μmoles/min/g of protein), exposed to thehighest concentration of profenofos. BuChE activity was also reduced against various concentrations of profenofos. The AChE andBuChE activity was significantly inhibited even when exposed to a minimum concentration of this insecticide. Profenofos exposureaffected the functioning of brain, blood, gills, muscle, kidneys and liver. We concluded that profenofos caused more inhibition in theliver for AChE and BuChE compared to other tissues.Conclusion: It has been concluded that profenofos is very highly toxic to the C. catla, L. rohita and C. mrigala fingerlings, but furtherstudies are required to assign a certain level of toxicity to the said pesticide. Considering the high toxicity of profenofos, it is suggested tohandle the profenofos carefully using all the precautionary measures in order to minimize the harmful effects on non-target organisms.